Insights into pyrolysis and catalytic co-pyrolysis upgrading of biomass and waste rubber seed oil to promote the formation of aromatics hydrocarbon. (23rd August 2018) - Zheng, Yunwu; Tao, Lei; Yang, Xiaoqing; Huang, Yuanbo; Liu, Can; Zheng, Zhifeng
Abstract: To solve the problem of low aromatic hydrocarbon yield and selectivity in biomass catalytic pyrolysis, we used added oxygen-containing hydrogen supplier of rubber seed oil (RSO) with a higher hydrogen-to-carbon ratio to investigate the thermal decomposition behaviors, kinetic and production distribution of biomass, cellulose and RSO with the weight ratio of 1:2 using thermogravimetric analyzer (TGA) for kinetic analysis and fixed bed reactor with the feed composition of 1.2 g: 0.4 mL/min (Biomass to RSO) for product distribution in non-catalytic and catalytic co-pyrolysis over a HZSM-5 catalyst. The results show that there was a positive synergistic interaction between biomass and RSO according to the difference in weight loss, which could decrease the formation of solid coke at the end of experiment. The addition of the HZSM-5 catalyst can markedly increase the reaction activity, accelerate the reaction rate, and the reaction Ea, leading to a substantial increase in the conversion rate; furthermore, the residual carbon content will decrease, and the activations of Cellulose + RSO + Catalyst and Biomass + RSO + Catalyst are only 50.80 kJ/mol and 62.36 kJ/mol, respectively. The kinetic analysis showed that adding a catalyst did not change the decomposition mechanism. Co-pyrolysis of biomass and RSO could effectively improve the yield and selectivity of aromatics, when the pyrolysis temperature and catalytic temperature were 550 °C and 500 °C, respectively, the mass space velocity of RSO was 0.4 mL/min, the reaction time was 30min, the yields of benzene, toluene, xylene and ethyl benzene (BTXE) were up to 78.77%, and the selectivity of benzene, toluene and xylene was much better. Finally, the coke yield was substantially lower. Highlights: TGA and fixed-bed were used to estimate the co-pyrolysis behavior of biomass and RSO. The interaction could accelerate k and decrease Ea compared with calculated results. The co-pyrolysis performance was optimized by varying operating parameters for BTXE. The proportion of BTXE in the bio-oil reached up to 78.77% under optimal conditions.